The Moderating Effect of Personality Traits on the Relationship Between Management Practices, Leadership Styles and Safety Performance in Iraq - Khdair, Wameedh A. (2013)
Existing literature reveals a gap in the empirical knowledge on safety performance in the oil and gas (O&G) industry in Iraq. This study specifically aims to identify the level of safety performance in the Iraqi O&G industry by examining the direct relationship among management practices (safety training, rewards, management commitment, communication and feedback, hiring practices, and employee participation), leadership styles (transformational and transactional), and safety performance (compliance with safety behavior and safety participation) among 713 employees. This study also explores the role of personality traits (extraversion, conscientiousness, intellect, agreeableness, and emotional stability) as a moderator of the relationship among management practices, leadership styles, and safety performance. Quantitative data were processed using the Statistical Package for Social Science version 18.0, which includes descriptive statistics, factor analysis, and Pearson correlation. Additionally, multiple regression and hierarchical multiple regressions were used to test the study hypotheses. In identifying interaction effects, significant beta coefficients and post hoc probing by split sample analysis were employed. Results provide general support for the hypothesis of the study, despite a number of differences in the direction of the relationships. Specifically, training, rewards, management commitment, communication and feedback, hiring practices, employee participation, and the transactional leadership style positively related to safety performance, whereas the transformational leadership style did not significantly relate to safety performance. The results also suggest that personality traits have a positive and significant moderating influence on the model. The relationship among management practices, leadership styles, and safety performance indicates that the improvement of safety performance through the management of employees will be beneficial to the Iraqi O&G industry. Finally, this study discusses theoretical and practical implications, as well as recommendations for future research.